Modelling climate change impacts on distribution of Himalayan pheasants. (April 2021) - Chhetri, Bijoy; Badola, Hemant Kumar; Barat, Sudip
Highlights: Species-specific response of climate change remains poorly documented in Himalaya. The pheasant range shifts trend in higher altitude and latitude become prominent. Among the three pheasants in future, two pheasants' habitats slightly shrunk. Effectiveness measures of the protected areas for the species seemed inadequate. Abstract: Well known at landscape regions, the environmental change will influence the mountain ecosystem around the globe. The impacts of climate change on animal-specific interaction remain inadequately reported. For the assessment of mountain biological systems, environmental models assume a significant job in recognizing and monitoring critical habitat under the potential future climatic conditions. Our paper, utilizing the Representative Concentration Pathways (RCPs-2050), the future global warming climatic scenarios, explores the trend of range shifts of Himalayan pheasants in the Eastern Himalayas based on an ensemble technique. The prediction model demonstrated that the core zone habitat of the Himalayan pheasants would have shifted towards higher altitude and latitude gradients with the greenhouse gaseous intensification. Under the extreme future climatic scenario, the species may reach towards Sky Island of the Himalayan regions. Therefore, a legitimate policy is essential to implement on time for the mitigation of the greenhouse gaseous emission. The outcome of this article illuminated that the present protected areas (PAs) of the Eastern Himalayas appeared to be inadequate regarding conservation measures of Himalayan Pheasants due to the current range may go rapidly beyond the protected zones. The shifting of the range of the Himalayan pheasants under future climatic scenarios will offer an indication for conservation directives to formulate appropriate strategies for habitat management of the threatened animals of the Himalayan ecosystem before the door of annihilation.